2019
DOI: 10.1111/hepr.13386
|View full text |Cite
|
Sign up to set email alerts
|

Weighted gene coexpression network analysis reveals hub genes involved in cholangiocarcinoma progression and prognosis

Abstract: AimCholangiocarcinoma (CCA) is a highly malignant tumor found in the bile duct epithelial cells, and the second most common primary tumor of the liver. However, the pivotal roles of molecular biomarkers in oncogenesis of CCA are unclear. Therefore, we aim to explore the underlying mechanisms of progression and screen for novel prognostic biomarkers and treatment targets.MethodThe data of mRNA sequencing and clinical information of CCA patients in The Cancer Genome Atlas was analyzed by weighted gene coexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Until now, our understanding of the complex mechanisms of CCA is still limited. One study using CCA data also analyzed the genes implicated in CCA (Tian et al, 2019). They dissected the genome network by other bioinformatic tool to explore the protein–protein interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, our understanding of the complex mechanisms of CCA is still limited. One study using CCA data also analyzed the genes implicated in CCA (Tian et al, 2019). They dissected the genome network by other bioinformatic tool to explore the protein–protein interaction.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways are well documented as participating in the carcinogenesis and progression of CCA [36]. Various studies based on multiple CCA independent cohorts [37][38][39] also detected that metabolic-related biological processes including small molecule and lipid metabolic processes relate to energy metabolism were pivotal for CCA development. Increasing evidence has demonstrated that fatty acids synthesis related genes (FASN and SLC27A1) [40,41], fatty acid transport proteins (FATP2, FATP1, FATP5, and CD36), and fatty acid binding proteins (FABP1, FABP4, and FABP5) [42] contribute to CCA carcinogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…To further evaluate the performance of the Fisher score algorithm, a series of control feature selection algorithms were utilized to select feature genes from the current integrated HCC dataset. The algorithms for comparison included WGCNA 54 , Lasso 55 , ReliefF 56 and random forest 57 .…”
Section: Methodsmentioning
confidence: 99%